2009
DOI: 10.1371/journal.pbio.1000041
|View full text |Cite
|
Sign up to set email alerts
|

Neto1 Is a Novel CUB-Domain NMDA Receptor–Interacting Protein Required for Synaptic Plasticity and Learning

Abstract: The N-methyl-D-aspartate receptor (NMDAR), a major excitatory ligand-gated ion channel in the central nervous system (CNS), is a principal mediator of synaptic plasticity. Here we report that neuropilin tolloid-like 1 (Neto1), a complement C1r/C1s, Uegf, Bmp1 (CUB) domain-containing transmembrane protein, is a novel component of the NMDAR complex critical for maintaining the abundance of NR2A-containing NMDARs in the postsynaptic density. Neto1-null mice have depressed long-term potentiation (LTP) at Schaffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
202
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(218 citation statements)
references
References 73 publications
11
202
5
Order By: Relevance
“…We elucidated the role of this association and characterized its importance in the normal neurophysiological function of KCC2. Because Neto proteins were previously identified as auxiliary subunits of ionotropic glutamate receptors, including kainate and NMDA receptors (17)(18)(19)(20)(21), this study further extends the role of the Neto proteins to inhibitory synapses.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…We elucidated the role of this association and characterized its importance in the normal neurophysiological function of KCC2. Because Neto proteins were previously identified as auxiliary subunits of ionotropic glutamate receptors, including kainate and NMDA receptors (17)(18)(19)(20)(21), this study further extends the role of the Neto proteins to inhibitory synapses.…”
mentioning
confidence: 70%
“…Recent reports have demonstrated that Neto2 and its homologous protein Neto1 have important functions at excitatory synapses. Neto1 interacts with both the N-methyl D-aspartate receptor (NMDAR) and kainate receptor complexes (17,20,22), whereas Neto2 was shown to be an auxiliary subunit of the neuronal kainate receptor (18,(21)(22)(23). As the Neto proteins appear to have multiple functions in the nervous system, we chose to explore additional roles these proteins might have by conducting an unbiased screen to identify proteins that interact with the Neto proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Neto1 possesses a single transmembrane domain containing two complement C1r/C1s, Uegf, Bmp1 domains and is a component of the NMDA receptor complex (Ng et al, 2009). Neto1 interacts with an extracellular domain of GluN2 as well as through an intracellular interaction with PSD95.…”
Section: H Transmembrane ␣-Amino-3-hydroxy-5-methyl-4-isoxazolepropimentioning
confidence: 99%
“…PSD95 also binds to the auxiliary subunit Neto1 [84], and accelerates the recovery of GluK2 from desensitisation [85]. The KAR component of the EPSC at MF-CA3 synapses is reduced in PSD95 knockout mice, suggesting a role for this interaction in KAR synaptic localisation [86].…”
Section: Psd95mentioning
confidence: 99%